Molecular Modeling of CO2 and n-Octane in Solubility Process and α-Quartz Nanoslit - Pu, Jun; Qin, Xuejie; Gou, Feifei; Fang, Wenchao; Peng, Fengjie; Wang, Runxi; Guo, Zhaoli (Energies (Basel), 2018)
After primary and secondary oil recovery, CO2-enhanced oil recovery (EOR) has become one of the most mentioned technologies in tertiary oil recovery. Since the oil is confined in an unconventional reservoir, the interfacial properties of CO2 and oil are different from in conventional reservoirs, and play a key role in CO2 EOR. In this study, molecular dynamics simulations are performed to investigate the interfacial properties, such as interfacial tension, minimum miscibility pressure (MMP), and CO2 solubility. The vanishing interfacial tension method is used to get the MMP (~10.8 MPa at 343.15 K) which is in agreement with the reported experimental data, quantitatively. Meanwhile, the diffusion coefficients of CO2 and n-octane under different pressures are calculated to show that the diffusion is mainly improved at the interface. Furthermore, the displacement efficiency and molecular orientation in α-quartz nanoslit under different CO2 injection ratios have been evaluated. After CO2 injection, the adsorbed n-octane molecules are found to be displaced from surface by the injected CO2 and, then, the orientation of n-octane becomes more random, which indicates that and CO2 can enhance the oil recovery and weaken the interaction between n-octane and α-quartz surface. The injection ratio of CO2 to n-octane is around 3:1, which could achieve the optimal displacement efficiency.